Hot carrier dynamics in perovskite nanocrystal solids: role of the cold carriers, nanoconfinement, and the surface - Hopper, Thomas R.; Gorodetsky, Andrei; Jeong, Ahhyun; Krieg, Franziska; Bodnarchuk, Maryna I.; Maimaris, Marios; Chaplain, Marine; Macdonald, Thomas J.; Huang, Xiaokun; Lovrincic, Robert; Kovalenko, Maksym V.; Bakulin, Artem A. (Nano letters, 2020)
Carrier cooling is of widespread interest in the field of semiconductor science. It is linked to carrier-carrier and carrier-phonon coupling and has profound implications for the photovoltaic performance of materials. Recent transient optical studies have shown that a high carrier density in lead-halide perovskites (LHPs) can reduce the cooling rate through a “phonon bottleneck”. However, the role of carrier-carrier interactions, and the material properties that control cooling in LHPs, is still disputed. To address these factors, we utilize ultrafast “pump-push-probe” spectroscopy on LHP nanocrystal (NC) films. We find that the addition of cold carriers to LHP NCs increases the cooling rate, competing with the phonon bottleneck. By comparing different NCs and bulk samples, we deduce that the cooling behavior is intrinsic to the LHP composition and independent of the NC size or surface. This can be contrasted with other colloidal nanomaterials, where confinement and trapping considerably influence the cooling dynamics.
Gesehen am 15.05.2020